Proceedings of the 2nd International Conference on Educational Sciences (ICES 2018) 2019
DOI: 10.2991/ices-18.2019.25
|View full text |Cite
|
Sign up to set email alerts
|

Management of Premarital Education to Build Readiness to Marry Youth in the Community Education Perspective

Abstract: Implementation of premarital education programs answers the facts of the problems that often occur in the community, especially the lack of premarital guidance to adolescents. Based on preliminary studies, the reasons that often arise from young people are the need for substantial costs to participate in premarital training programs, not least that premarital education conducted by KUA is still limited and not even directly felt by the community. Through the practicum of the course with a project based learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Considering that marriage at a young age was not necessarily accompanied by mental readiness (Badruzaman, 2021) or economic readiness (Agustian, 2013), the purposes of this program were also to No 1, February 2024: 178-192 advocate premarital education and awareness on the issues concerning young people's preparedness for marriage (Ardiwinata et al, 2019). Some previous studies found that pre-marriage education escalated the quality of relationships in marriage (Carroll & Doherty, 2003) and could predict marital satisfaction levels (Stanley et al, 2006;Yilmaz & Kalkan, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that marriage at a young age was not necessarily accompanied by mental readiness (Badruzaman, 2021) or economic readiness (Agustian, 2013), the purposes of this program were also to No 1, February 2024: 178-192 advocate premarital education and awareness on the issues concerning young people's preparedness for marriage (Ardiwinata et al, 2019). Some previous studies found that pre-marriage education escalated the quality of relationships in marriage (Carroll & Doherty, 2003) and could predict marital satisfaction levels (Stanley et al, 2006;Yilmaz & Kalkan, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that marriage at a young age was not necessarily accompanied by mental readiness (Badruzaman, 2021) or economic readiness (Agustian, 2013), the purposes of this program were also to advocate premarital education and awareness on the issues concerning young people's preparedness for marriage (Ardiwinata et al, 2019). Some previous studies found that pre-marriage education escalated the quality of relationships in marriage (Carroll & Doherty, 2003) and could predict marital satisfaction levels (Stanley et al, 2006;Yilmaz & Kalkan, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Psychoeducation program "Me and Marriage: Marriage with Preparation" as a prevention of early marriage Vidya Anindhita, Hendriati Agustiani, Langgersari Elsari Novianti, Ajeng Nuranti Syafitri advocate premarital education and awareness on the issues concerning young people's preparedness for marriage (Ardiwinata et al, 2019). Some previous studies found that pre-marriage education escalated the quality of relationships in marriage (Carroll & Doherty, 2003) and could predict marital satisfaction levels (Stanley et al, 2006;Yilmaz & Kalkan, 2010).…”
Section: |mentioning
confidence: 99%